Trust in Media and Journalism Empirical Perspectives on Ethics, Norms, Impacts and Populism in Europe (Springer Fachmedien Wiesbaden : VS, 2018)
All over Europe and the World communication scientists reflect questions on trust in journalism and media. A large scale of analysis and research gives new perspectives of reasons, impacts and consequences of trust or mistrust in media and journalism. This anthology provides an overview on empirical research to trust in media and journalism, new perspectives, methodological approaches and current results, discussed among communication scientists at European and international scientific conferences. Contents Ethics and Norms Impacts on Trust Populism Target Groups Lecturers and students of communication sciences Journalists The Editors Prof. Dr. Kim Otto is Professor for economics journalism at the University of Würzburg. Dr. Andreas Köhler is Research associate at the chair for economics journalism at the University of Würzburg.